Penerapan Strategi Promotion Mix pada Rumah Makan Best Eating House - Lily Purwianti; Lidya Siska Khoviati (Universitas Internasional Batam, 2021)
In the past, the use of conventional marketing systems was often used by business owners to increase business in the sense of carrying out a face-to-face promotion system. However, the development of technology has made the system less being used but a new marketing system has emerged that makes it easier for a business to promote its products or services where this system is only sufficient to take advantage of one's creativity and one's intention to carry it out. Best Eating House Restaurant still relies on this conventional marketing system. Therefore, the authors want to implement a marketing mix system at the restaurant so that the restaurant has increased sales by 10% every day. The method used is in the form of training (training) for business owners. In this case, the author will design strategies that in the future can be utilized by business owners in the long term, namely designing food and beverage menus with contemporary themes, creating an Instagram account with business account status, compiling aesthetic food menu dishes in the Instagram feed and uploading them to the Instagram story, make highlights on Instagram to make it easier to search, and design stamp cards for visitors where if you have got a stamp of 5x @ IDR 30,000 then free screwdriver tea drinks